2020
DOI: 10.1093/jisesa/ieaa066
|View full text |Cite
|
Sign up to set email alerts
|

Increased Responses of Phenoloxidase in Chlorantraniliprole Resistance of Plutella xylostella (Lepidoptera: Plutellidae)

Abstract: Abstract The diamondback moth (Plutella xylostella, DBM) is an important pest of cruciferous vegetables. The use of chlorantraniliprole has been essential in the management of the DBM. However, in many countries and areas, DBM has become highly resistant to chlorantraniliprole. Three different DBM strains, susceptible (S), chlorantraniliprole-selected (Rc), and field-collected (Rb) resistant strains/populations were studied for the role of phenoloxidase in resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
1
5
0
1
Order By: Relevance
“…The tested formulations could induce oxidative stress and apoptosis in various non-nerve tissues [43,45].…”
Section: Discussionmentioning
confidence: 99%
“…The tested formulations could induce oxidative stress and apoptosis in various non-nerve tissues [43,45].…”
Section: Discussionmentioning
confidence: 99%
“…Its activity is an important marker of mosquito immunity (Rodriguez‐Andres et al, 2012). Therefore, the determination of PO activity should estimate immune status and insecticide resistance (Wang et al, 2020). To the best of our knowledge, this study is the first in Egypt to investigate the impact of insecticide resistance on the mosquito immune system comparing two Cx.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent applications of diamide insecticides have resulted in the selection of diamide resistance in field populations of H. armigera 40 , S. exigua, 26,47 P. xylostella, 58,60 C. suppressalis 61 and Tuta absoluta (Meyrick), 62 and excellent control efficacies have not been produced by rotating different MoA chemistries. For example, Ahmad et al 30 reported that H. armigera had very low resistance levels to chlorantraniliprole (1.8-to 6.8-fold at LC 50 ) during 2010-2016 and to flubendiamide (1.5-to 8.2-fold at LC 50 ) during 2009-2016.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent applications of diamide insecticides have resulted in the selection of diamide resistance in field populations of H. armigera 40 , S. exigua , 26,47 P. xylostella , 58,60 C. suppressalis 61 and Tuta absoluta (Meyrick), 62 and excellent control efficacies have not been produced by rotating different MoA chemistries. For example, Ahmad et al 30 .…”
Section: Discussionmentioning
confidence: 99%